Competency Level of Special Education Integration Program Teachers in Conducting Assessment on Students with Learning Disabilities - Nadiah Abu Bakar; Mohd Mokhtar Tahar (Journal of ICSAR, 2019)
The purpose of this research was to identify the level of knowledge, skills and attitude of the Integrated Special Education Program (PPKI) teachers in conducting assessment of students’ learning disabilities in four primary schools in the Federal Territory of Kuala Lumpur, Malaysia. This research is based on Theory of Behaviorism founded by Thorndike and Iceberg Competency Model. The research design was quantitative with the population consisting of 50 PPKI teachers while the samples of the research were 44 teachers selected by simple random sampling method. The instrument was a questionnaire adapted from Sulaiman (2008) and confirmed with Alpha Cronbach. The data were analyzed using descriptive statistics, percentage, frequency and mean. The results showed that the level of knowledge of PPKI teachers was high with mean score, the level of skill was moderate, and the level of attitude was high. It is concluded that PPKI teachers have good knowledge of the assessment process on students with learning disabilities but require additional training and courses to improve their skills.